Barreiras à implementação de recomendações para assistência ao parto normal: revisão rápida de evidências - Oliveira, Cintia de Freitas (Rev Panam Salud Publica, 2020)
OBJECTIVE. To identify potential barriers to the implementation of the National Childbirth Guidelines in Brazil based on the best available global evidence. METHOD. A rapid review of evidence was performed in six databases in March/April 2019. Secondary studies published in English, Spanish, or Portuguese with a focus on barriers of any nature relating to the implementation of the Guidelines were retrieved. RESULTS. Twenty-three documents (21 reviews and two practice guides) were included in the review. The barriers identified were grouped into 52 meaning categories and then reorganized into nine thematic clusters: delivery and childbirth care model, human resource management, knowledge and beliefs, gender relations, health care service management, attitudes and behaviors, communication, socioeconomic conditions, and political interests. CONCLUSIONS. The results show that combined approaches may be required to address different barriers to the implementation of the Guidelines. For successful implementation, it is essential to engage health care leaders, professionals, and users in the effort to change the delivery and childbirth care model. Also necessary is the development of intersectoral initiatives to improve the socioeconomic conditions of women and families and to curtail gender inequalities.